Human Uniqueness: Standing Alone?. (October 2015) - Davidson, Andrew
Discussion of human uniqueness requires careful attention to what 'uniqueness' means. The word is commonly deployed as meaning both distinctiveness and superiority, which implies contrasting relations of continuity and distinction between what is 'unique' and what it is contrasted with. Human uniqueness has come into sharp focus in recent years because of discussions of 'exobiology': life beyond Earth. Intelligence has frequently been put forward as definitive of human uniqueness, but the 'convergent evolution' of intelligence suggests that intelligence would also evolve elsewhere, leaving human beings unique neither as to distinctiveness nor to excellence. However, while evolution might be convergent over basic characteristics such as intelligence, to how the body is structured seems to be more contingent, and we must take the role of the body's role in thought ('embodied cognition') seriously. Basic bodily differences between putative life-forms might, therefore, lead to strong distinctions between the forms that intelligence takes. Human beings might not be 'unique as superior', but they would be unique as distinct, bodily speaking, and that distinction might be strongly determinative of the way in which intelligence is worked out.